The stalled revolution : is equality for women an impossible dream? - Tutchell, Eva; Edmonds, John (Emerald Publishing Limited, 2025)
In this eagerly anticipated second edition of The Stalled Revolution, authors Tutchell and Edmonds build upon their groundbreaking exploration of the Votes for Women campaign and the Women's Liberation movement, by focusing on the dramatic activities of the #MeToo movement and on the passionate debate about trans and gender identity. The #MeToo movement has swept aside the long-standing conspiracy of silence about sexual abuse, revealing its vast extent and terrible effects. Unveiling the origins of #MeToo and scrutinizing its impact, this second edition offers a balanced perspective on the movement's accomplishments and assesses its future challenges. A new thought-provoking section unravels the interwoven strands of the trans debate and uncovers the unexpected truth that, despite the hostile language, much common ground exists between the two sides. By redefining the issues, Tutchell and Edmonds show how a more optimistic discourse on identity, gender, and the rights of transgender individuals can be developed. Based on the successes of the suffragists, the Women's Liberation Movement, and the #MeToo movement, this new narrative envisions a future of enhanced equality and empowerment. Offering a blueprint for a dynamic, comprehensive campaign, The Stalled Revolution stands as a thought-provoking testament to the ongoing struggle for women's rights and a catalyst for change.